Fostering Student-Centered Math Classrooms: The Role of Kahoot in Optimizing Academic Performance - Budi Sarjana; Fatikhatun Nikmatus Sholihah; Ospa Pea Yuanita Meishanti (Indonesian Journal of Progressive Pedagogy, 2026)
The integration of digital learning technologies has become increasingly important for fostering interactive and student-centered learning environments. This study aims to examine the effectiveness of Kahoot as an interactive learning medium in improving students’ motivation, learning activities, and mathematics learning outcomes. The research employed a mixed-methods sequential explanatory design involving 32 seventh-grade students and two mathematics teachers. Quantitative data were collected through pre–post tests, motivation questionnaires, and classroom observation sheets, while qualitative data were obtained through semi-structured interviews and documentation. The results showed significant improvements in students’ learning outcomes, with the mean score increasing from 52.33 to 78.67 and mastery achievement rising from 33.3% to 90%. Learning motivation increased from a mean score of 61.2 to 82.5, while classroom participation improved from 30% to 100%. These findings indicate that Kahoot effectively enhances cognitive, motivational, and behavioral aspects of learning. The study contributes to the literature by integrating cognitive and engagement dimensions within a mixed-methods framework and recommends integrating gamified digital platforms into mathematics instruction.